Description of three new species of the deep-sea munnopsid genus Belonectes (Crustacea, Isopoda, Asellota) from the Weddell Sea, Southern Ocean - Malyutina, Marina V.; Brandt, Angelika (Zootaxa, 2009)
Three new species of the genus Belonectes Wilson & Hessler, 1981, from the munnopsid subfamily Eurycopinae Hansen are described from the deep Weddell Sea, Atlantic sector of the Southern Ocean. Belonectes grasslei sp. nov., B. stoddarti sp. nov., and B. daytoni sp. nov. are the first species of the genus described from the region: previously only two species of Belonectes were known from the northeastern Atlantic and the Peru-Chile Trench, the southeastern Pacific. The modified diagnosis of the genus Belonectes and a key to the species of the genus are presented. The pattern of the total ventral sculpture of the natasome, a medial lobe of article 4 of the maxillipedal palp which is larger than article 5 and the navicular male pleopod 1 with its deep keel are suggested to be additional important generic characters of Belonectes. The most useful characters to distinguish species of Belonectes are the size of article 1 of the antennula, the shape and size of the articles 3–5 of the maxillipedal palp, the shape of the distal margin of the male pleopod 1, the shape of distolateral part of the protopod of the male pleopod 2, the size and shape of the preanal ridge, and the size of the exopod of the uropod.